Translation and Validation of Short Version of Freiburg Mindfulness Inventory (FMI-14) - Pérez-Verduzco, Germán; Laca-Arocena, Francisco Augusto (Revista Evaluar, 2017)
In recent years, interest in studying Mindfulness and its relationship with subjective well-being has increased. In addition, evaluation of this construct is becoming more common in clinical practice, in order to design interventions to enhance physical and psychological health. In this study, the short version of Freiburg Mindfulness Inventory (FMI-14) has been translated and validated. The study sample consisted of 200 Mexican individuals, from both university and non-university settings. The scale was analyzed with various statistical methods, including exploratory factor analysis (EFA) and confirmatory factor analysis (CFA). Four components of Mindfulness, hereby called attention, self-control, acceptance, and self-perception were found by using EFA. Subsequently, by using CFA, we found that this model had a good fit (CFI = .93; GFI = .93; AFGI = .89; SRMR = .05; RMSEA = .04). Finally, our results show that our instrument is reliable (? = .80) and valid to assess Mindfulness in Spanish-speaking population.